Morningstar funds 500 : (Morningstar, Inc., 2008)
In this completely new reference guide, you’ll find the best information and independent opinion available on 500 of the largest and most popular mutual funds—the very funds you likely own. Morningstar’s Fund Reports are the industry standard and are trusted by financial professionals nationwide. And now, you get this exclusive and valuable guidance all year long, with access to fifty free fund reports during any time in 2008. Choose from 2,000 funds.